2014
DOI: 10.1371/journal.pone.0112532
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Promote Liver Regeneration and Prolong Survival in Small-For-Size Liver Grafts: Involvement of C-Jun N-Terminal Kinase, Cyclin D1, and NF-κB

Abstract: BackgroundThe therapeutic potential of mesenchymal stem cells (MSCs) has been highlighted recently for treatment of acute or chronic liver injury, by possibly differentiating into hepatocyte-like cells, reducing inflammation, and enhancing tissue repair. Despite recent progress, exact mechanisms of action are not clearly elucidated. In this study, we attempted to explore whether and how MSCs protected hepatocytes and stimulated allograft regeneration in small-for-size liver transplantation (SFSLT).MethodsSFSLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
(88 reference statements)
3
29
0
Order By: Relevance
“…Significantly, the AP-1 transcription factor is at the hub of the signalling network. Jun proteins preferentially regulate genes involved in proliferation and apoptosis, including Bim (34), Bcl-3 (35) and cyclin D1 (36), whereas Fos proteins, including DNA (cytosine-5)-methyltransferase 1 (37) and matrix metalloproteinase 1, are often required for angiogenesis and invasion by malignant tumours (38). To clarify the factors involved in gemcitabine-induced apoptosis, we analysed c-Jun and c-Fos.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, the AP-1 transcription factor is at the hub of the signalling network. Jun proteins preferentially regulate genes involved in proliferation and apoptosis, including Bim (34), Bcl-3 (35) and cyclin D1 (36), whereas Fos proteins, including DNA (cytosine-5)-methyltransferase 1 (37) and matrix metalloproteinase 1, are often required for angiogenesis and invasion by malignant tumours (38). To clarify the factors involved in gemcitabine-induced apoptosis, we analysed c-Jun and c-Fos.…”
Section: Discussionmentioning
confidence: 99%
“…Under different induction environments, they can differentiate into osteoblasts, adipocytes, chondroblasts and neuroblasts (2). Studies have indicated that BMSCs are the source of osteoblasts and osteocytes (3,4). Inducing BMSCs to differentiate directionally is of significance to curing inflammatory bone disease and repairing bone loss (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…[128]. MSCs accelerate liver regeneration through complement C3, EGFR and thioredoxin [129]. For restoration of portal vein hepatic circulation growth factors [hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), insulin-likegrowth factor 1 (IGF-1), insulin-like growth factor binging protein 3 (IGF-BP3), epidermal growth factor (EGF), transforming growth factor (TGFα), tumor necrosis factor (TNF)] and interleukins (IL2, -6, -8 and -10) play important role [130].…”
Section: Therapeutic Role Of Cell Secreted Growth Factorsmentioning
confidence: 99%